2013
DOI: 10.1016/j.cell.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of BAD by IKK Inhibits TNFα-Induced Apoptosis Independently of NF-κB Activation

Abstract: Summary The IκB kinase complex (IKK) is a key regulator of immune responses, inflammation, cell survival, and tumorigenesis. The pro-survival function of IKK centers on activation of the transcription factor NF-κB, whose target gene products inhibit caspases and prevent prolonged JNK activation. Here we report that inactivation of the BH3-only protein BAD by IKK independently of NF-κB activation suppresses TNFα-induced apoptosis. TNFα-treated Ikkβ−/− mouse embryonic fibroblasts (MEFs) undergo apoptosis signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 48 publications
4
93
1
Order By: Relevance
“…For example, IKKβ can inhibit cell death in an NF-κB-independent manner by phosphorylating BAD, a BH3-only proapoptotic protein, to prime it for inactivation (40). We also found that IKKβ phosphorylation of BAD is important for adipocyte survival in obesity (34).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…For example, IKKβ can inhibit cell death in an NF-κB-independent manner by phosphorylating BAD, a BH3-only proapoptotic protein, to prime it for inactivation (40). We also found that IKKβ phosphorylation of BAD is important for adipocyte survival in obesity (34).…”
Section: Discussionmentioning
confidence: 48%
“…Although much attention has been focused on the NF-κB-dependent functions of IKKβ, IKKβ can regulate inflammation, apoptosis, cell proliferation, and metabolic homeostasis through NF-κB-independent mechanisms by phosphorylating other key molecules such as SNAP-23, IRF7, p53, BAD, and XBP1 (39,40,57). For example, IKKβ can inhibit cell death in an NF-κB-independent manner by phosphorylating BAD, a BH3-only proapoptotic protein, to prime it for inactivation (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functions for IKK2 other than NF-κB activation have been described in other cell types (23). We therefore wished to assess whether IKK2 was regulating IL-7Rα expression in peripheral T cells by activating NF-κB signaling.…”
Section: Ikk2mentioning
confidence: 99%
“…TNF-a has pleiotropic functions in inflammatory progression depending on cell type or biological context 7 . In certain conditions, TNF-a induces apoptosis; however, recent studies have indicated that TNF-a may promote hepatocellular carcinogenesis by activating a variety of signal pathways related to cell proliferation, differentiation and survival [8][9][10] . The mechanism of inflammation linked to TNF-a and involved in hepatocellular carcinogenesis still needs to be fully elucidated.…”
mentioning
confidence: 99%